Management of the Nationality Center as an Effort to Instill the Value of Love for the Homeland in Early Childhood at TK Al-Azhar Syifa Budi Samarinda - Aulia, Novi; Karmila, Karmila; Berliana, Berliana; Bunga, Bunga; Kamsiana, Sitti; Sjamsir, Hasbi; Rozie, Fachrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This research was conducted with the aim of deeply examining the management of the Nationality Center (Sentra Kebangsaan) as a strategy for cultivating the values of love for the homeland (cinta tanah air) in early childhood at TK Al-Azhar Syifa Budi Samarinda. The background for this study stems from the awareness that early childhood education plays a fundamental role in shaping character, morals, and national identity from the initial stages of growth. Instilling a sense of national pride must be designed through learning experiences that are engaging, relevant to daily life, and meaningful to the child. This study uses a descriptive qualitative approach, involving two main informants: the school principal and a teacher from Kindergarten A who is directly involved in managing the Nationality Center. Data collection was performed through in-depth interviews, field observations, and documentation review, such as the Daily Lesson Implementation Plan (RPPH) and records of children’s activities. Data analysis followed the stages of the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The results show that the management system of the Nationality Center at TK Al-Azhar Syifa Budi Samarinda comprises: planning learning programs oriented toward national values, implementing play activities that foster a spirit of nationalism, and continuous evaluation to strengthen the child’s character of love for the homeland. With structured and consistent management, the Nationality Center functions as a strategic educational vehicle that plays a role in building national identity, moral attitudes, and a sense of pride in the nation since the preschool age.